Determination of the excitation functions for nuclear reactions induced by helium-3 in lithium - Grilo, José Francisco Gonçalves (2023)
Since a few decades, nuclear fusion has been considered a promising alternative power source, but the technology behind it is still in a preliminary phase of development. Some technological challenges must still be overcome, namely in the components of the fusion reactor facing the plasma, where lithium might play an important role, especially as a tritium breeder, since tritium, an important isotope for nuclear fusion, is a scarce resource. Eventually, these components containing lithium will need to be characterized. Therefore, in 2020, the International Atomic Energy Agency (IAEA) created a Coordi- nated Research Project (CRP) devoted to the “Development and Application of Ion Beam Techniques for Materials Irradiation and Characterization relevant to Fusion Technology” (CRP Code F11023). The determination of the excitation functions for the nuclear reactions induced by 3He in 6Li, 7Li, 9Be , 10B, 11B , 12C and 13C was set as project priority due to lack of data and poor agreement among already existing datasets. The present work makes a contribution to the goals of the CRP by determining the excitation functions for the following nuclear reactions: 6Li(3He, p0)8Be , 7Li(3He ,pi)9Be ( = 0, 2, 3, 4) and 7Li(3He ,d0)8Be . The spectra were acquired using two thin lithium films (one of 6Li and another of 7Li) in the energy range between 800 keV and 2500 keV (the typical energy range for ion beam analysis techniques) for scattering angles between 115° and 165° with a 10° step. The results were compared with data from the literature. Additionally, in this work, differential cross sections were determined for the elastic scattering of protons in 6Li, 7Li and 19F in the energy range between 620 keV and 2050 keV and for a scattering angle of 165°.